Assessing the Impact of Transformational Leadership and Employee Empowerment on Organisational Performance in the Indonesian Service Sector - Intiar, Septa (Sinergi International Journal of Management and Business, 2023)
This study investigates the relationships between transformational leadership, employee empowerment, and organizational performance in the Indonesian service sector. A quantitative research approach was adopted, and data were collected from 250 employees and managers using self-administered questionnaires. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze the data. The results reveal significant positive relationships between transformational leadership and employee empowerment, employee empowerment and organizational performance, and transformational leadership and organizational performance. Furthermore, mediation analysis indicates that a substantial portion of the influence of transformational leadership on organizational performance is mediated by employee empowerment. These findings highlight the importance of fostering transformational leadership behaviors and promoting a culture of empowerment to enhance organizational performance in the Indonesian service sector.